Effects of supplementing limit-fed, wheat middling-based diets with either soybean meal or non-enzymatically browned soybean meal on growing steer performance - C.M. Coetzer; E. Coetzer; R.H. Wessels; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1999)
Seventy two individually fed Angus x Hereford steers (660 lb) were limit-fed, 16.7% CP wheat middling-based diets with 1.9 or 3.8 percentage units of additional CP from either soybean meal (SBM) or non-enzymatically browned soybean meal (NEBSBM). A limitfed, rolled corn-based diet (16.7% CP) also was included. Steers were fed once daily for 70 days at 2.25% of BW. The SBM provided 30% bypass protein, and NEBSBM provided 68%. Average daily gain and efficiency improved linearly with increasing level of NEBSBM (P<.05; ADG=2.482 + .106 (increase in % CP); feed to gain=6.26 - .22(increase in % CP)), but not with increasing levels of SBM. Steers fed the wheat middling diets had lower ADG and efficiency than those fed the corn control diet. These data suggest that bypass protein may be first limiting in highconcentrate, limit-fed growing diets composed predominantly of wheat middlings.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Wheat middlings; Growing cattle; Undegraded intake protein